Comparison of Select Analytes from Different Laboratories in Tobacco and Smoke for Commercial Cigars Across a Range of Designs - Tayyarah Rana; Sirkisoon Leona R.; Gentry Lee (Contributions to Tobacco and Nicotine Research)
Analytical research relevant to cigar products is relatively limited compared to other tobacco product categories and very few standardized methods are in place. In recent years, scientific and regulatory interests in cigar testing have increased. Thus, there is a need for increased foundational knowledge in the product space. The objective of this work was to characterize cigars across a range of design features to understand relative magnitude of results and to evaluate analytical variability among and between three laboratories using their own practices and methodology.